International Collaboration in Scientific Debate - Wierzchosławski, Rafał (Zagadnienia Naukoznawstwa, 2024)
The discussion of the Scientific Cooperation took place during the pandemic summer months of 2020. Three prominent scholars, of various specialities gave their assesment not only of the context of the book in question itself, but also in institutional, social, and culturak context within which significant transformations of the academic world are taking place. These transforations determine in the functioning of modern science. In the first part, I present the profiles of scientific achievements of the participants in the discussion: Steven Turner, Nico Stehr and Steve Fuller. Then, I make a brief discussion of the content of the book under discussion. I pay particular attention to the aspects of center-periphery relations, which are important from the point of view of the Polish reader, and which define the types of cooperation in the global republic of scholars. Especially in the context of the possible advancement of peripheral centers in the hierarchy of important links which enable skilful cooperation with the centers. In the last section I draw attention to the forms of scientific cooperation practiced themselves by three scholars invited to discuss with Olechnicka et al.’s book, in the context of the types of man of knowledge distinguished years ago by Florian Znaniecki.